Comparison between functional and intravascular imaging approaches guiding percutaneous coronary intervention: A network meta‐analysis of randomized and propensity matching studies. Issue 7 (9th August 2019) - Iannaccone, Mario; Abdirashid, Mohamed; Annone, Umberto; Saint‐Hilary, Gaëlle; Meier, Pascal; Chieffo, Alaide; Chen, Sl; di Mario, Carlo; Conrotto, Federico; Omedè, Pierluigi; Montefusco, Antonio; De Benedictis, Michele; et al.
Abstract: Background: The optimal approach to guide percutaneous coronary intervention (PCI) has yet to be defined. The aim of this study was to compare functional driven (fractional flow reserve) versus intravascular imaging (intravascular ultrasound, IVUS, and/or optical coherence tomography, OCT) versus standard (coronary angiography only, CA)‐guided PCI. Methods: Randomized controlled trials (RCTs) and propensity score weight‐matched studies (PSWMs) comparing FFR versus IVUS versus OCT versus CA‐guided PCI were included. Major adverse cardiovascular event (MACE; a composite end point of death or myocardial infarction [MI] or revascularization) was the primary endpoint, whereas definite stent thrombosis (ST) and single components of MACE were the secondary ones. Primary analyses were performed including only RCTs, secondary also with PSWMs. Results: Thirty‐three studies were included in the analysis, 16 RCTs and 17 PSWMs. After 2 (1–3) years, IVUS performed better for MACE than CA (odds ratio [OR] 0.75 0.52–0.88), whereas there was just a trend for FFR (OR 0.81, 0.64–1.02). These results were mainly driven by reduced risk of all cause death, MI (FFR OR 0.74:0.57–0.99 and IVUS OR 0.82:0.54–0.94) and revascularization. IVUS reduced ST while FFR did not, and at meta‐regression analysis, there was a trend for superiority of IVUS versus FFR to reduce subsequent MI in acute coronary syndrome (ACS) patients. The present results were consistent also after adding studies with PSWMs. Conclusions: Functional and intravascular imaging approaches seem to perform similarly in term of clinical outcomes, while both performed better compared with the standard approach. Imaging showed a potential benefit for ACS patients. The present results stress the need for a wider use of functional or imaging driven PCI.